The mechanism of cryptolepine-induced cell death - Ansah, C.; Zhu, H.; Goderham, N. J. (Asian Network for Scientific Information, 2008)
The objective of the present study was to use morphological and biochemical approaches to characterize the mode of CLP-induced cell death. Using a differential staining technique, a Chinese Hamster fibroblast cell line (V79 cells) and a human lymphoblastoid cell line (MCL-5) showed morphology consistent with apoptosis after treatment with CLP. In contrast, HepG2, a human hepatoma cell line showed morphology that was more like necrosis after treatment with CLP. Using annexin V staining for apoptotic cells, MCL-5 cells showed a three fold increase in apoptosis within 6 h. Although we observed only a marginal increase in BAX protein expression, cytochrome c was released into the cytosol of CLP-treated MCL-5 cells. Furthermore, procaspase-3 was processed into the active caspase-3 (17 kDa). Consistent with the caspase-3 activation, PARP was cleaved to the typical 85 kDa fragment confirming apoptosis as the mode of cell death in CLP-treated MCL-5 cells. However, there was no evidence of increased BAX expression, cytochrome c release, caspase activation or PARP cleavage in CLP-treated HepG2 cells. This observation together with the morphology of CLP- treated HepG2 cells indicates that in contrast to MCL-5 cells, the CLP-mediated demise of HepG2 cells is not apoptotic.